A one-pot multicomponent approach to a new series of morphine derivatives and their biological evaluation. Issue 37 (6th September 2017) - Shao, Jiaan; Houghten, Richard A.; Dooley, Colette T.; Cazares, Margret; McLaughlin, Jay P.; Eans, Shainnel O.; Ganno, Michelle L.; Hoot, Michelle R.; Giulianotti, Marc A.; Yu, Yongping
Abstract : Morphine derivatives displaying a mixed MOR/DOR biological characteristic were synthesized through a one-pot multicomponent approach. Abstract : A novel and facile domino reaction has been developed to synthesize a variety of new derivatives from hydromorphone, amines and paraformaldehyde in good yields in a catalyst-free fashion with high atom efficiency. The products show a mixed MOR/DOR biological characteristic which makes them valuable for further study as opioid analgesics.